Upaya Guru dalam Memberikan Pelayanan Pembelajaran Pendidikan Jasmani Olahraga Kesehatan pada Masa Tatap Muka Terbatas di SD Se-Kecamatan Kangkung - Priatmojo, Ilham Bagus (Universitas Negeri Semarang, 2023)
The purpose of the study was to find out the results of the efforts made by teachers in providing educational services carried out during a limited face-to-face learning period held in elementary schools throughout the Kangkung District, this study used descriptive qualitative research methods, and data collection techniques in this study weretdata collection techniques used include observation, interviews and documentation,Analysis of the data obtained is qualitative data in the form of a collection of tangible words. The results of the research carried out are in the limited face-to-face learning process, schools design learning according to the syllabus, lesson plans with an allocation of 3 hours of lessons, distance learning only 2 hours of lessons.During distance learning, teachers use student handbooks and internet media. Media and tools used by teachers in the learning process are whatsapp, zoom and smartphone applications. While the face-to-face learning period is limited to using student handbooks, internet media learning media such as whistles, balls, nets, cones, and stopwatches and audio and visual media, other sports equipment. In the limited face-to-face period the teacher teaches directly and deals with students with a 50% attendance, during the distance learning period via online. Assessment on face-to-face is limited directly with the rules of limiting the number of attendance, distance learning period assessment using whatsapp media.